2005
DOI: 10.2223/jped.1348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two prognostic scores (PRISM and PIM) at a pediatric intensive care unit

Abstract: Resultados: Internaram na unidade de terapia intensiva pediátri-ca 498 pacientes, sendo 77 excluídos. Dos 421 pacientes estudados, 33 (7,83%) foram a óbito. A mortalidade estimada pelo PRISM foi de 30,84 (7,22%), com standardized mortality rate 1,07 (0,74-1,50), z = -0,45. Pelo PIM, foi de 26,13 (6,21%), com standardized mortality rate 1,26 (0,87-1,77), z = -1,14. O teste de ajuste de Hosmer-Lemeshow obteve um qui-quadrado 9,23 (p = 0,100) para o PRISM e 27,986 (p < 0,001) para o PIM. A área abaixo da curva RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
(30 reference statements)
3
18
0
4
Order By: Relevance
“…The reasons for the under prediction and poor calibration of the PIM score could be considered to be the small number of deaths at each risk interval. 14,15 Eight variables in the PIM score recorded just at the time of admission may not represent the actual magnitude of the organ dysfunction leading to death. This could be the reason that the Standardized Mortality Ratio (SMR) of the present study population with PIM score was 3.3 as compared to 1 for the PRISM score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the under prediction and poor calibration of the PIM score could be considered to be the small number of deaths at each risk interval. 14,15 Eight variables in the PIM score recorded just at the time of admission may not represent the actual magnitude of the organ dysfunction leading to death. This could be the reason that the Standardized Mortality Ratio (SMR) of the present study population with PIM score was 3.3 as compared to 1 for the PRISM score.…”
Section: Discussionmentioning
confidence: 99%
“…Such disparity in the SMR on comparing the PIM and PRISM score has not been observed in other studies. 5,15 Due to the availability of a specialized emergency medical services (EMS) set-up at our facility, patients are often stabilized before they are transferred to the PICU. Moreover, it is ensured that the patients do not have unsteady physiological parameters during transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric risk of mortality (PRISM) score has been developed and validated in several centers in the United States in pediatric patients [9]-[11]. It was reported that the PRISM score could directly reflect the severity of the disease, and has been widely used for predicting patients’ death or survival, as reported in Portugal in 2005, the United Kingdom and Senegal in 2006, and India in 2010 [12]-[15]. …”
Section: Introductionmentioning
confidence: 99%
“…Although PRISM and PIM have been shown to be able to differentiate between survival and death in the ICU setting, the simulated model results have been found to be somewhat different from real situations and therefore Intensive Care Med (2012) 38:649-654 DOI 10.1007/s00134-011-2460-5 ORIGINAL needed standardization [3,[5][6][7][8][9][10][11][12]. Prior to implementation of these tools in a new country, it is important to examine their performance [13].…”
Section: Introductionmentioning
confidence: 99%